Development of novel Fe-based bulk metallic glasses with excellent wear and corrosion resistance by adjusting the Cr and Mo contents. (February 2023) - Zhang, Chengwu; Li, Qiang; Xie, Lei; Zhang, Guan; Mu, Baoxia; Chang, Chuntao; Li, Hongxiang; Ma, Xu
Abstract: In this work, a series of novel Fe80–x–y Crx Moy P10 C7 B3 (x = 0, y = 0; x = 0, y = 4; x = 5, y = 4; x = 15, y = 4; x = 20, y = 4; x = 15, y = 8 in at.%; denoted as Crx Moy ) bulk metallic glasses (BMGs) with critical diameters in the range 1.0–2.5 mm were fabricated. The effect of Cr and Mo contents on the glass forming ability (GFA), thermal stability, mechanical properties, corrosion behavior, and wear performance of the these Fe-based BMGs were systematically investigated. A partial substitution of Fe by Cr and Mo was found to enhance the GFA of the Fe-based BMGs. The sample Cr15 Mo4 exhibited the maximum critical diameter (2.5 mm), maximum temperature range of the supercooled liquid phase (55 K), and highest activation energy for the primary crystallization process (184 kJ·mol −1 ). Uniaxial compression and microhardness tests revealed that the compressive strength and Vickers microhardness of the Fe-based BMGs were in the range 3.0–3.7 GPa and 794–958 HV0.1, respectively, and increased with increasing Cr/Mo content. Electrochemical tests in a 3.5 wt.% NaCl solution showed that the Fe-based BMGs exhibited a significantly higher corrosion resistance than 316L stainless steel (316L SS) and 304L stainless steel (304L SS). The corrosion resistance of the Fe-based BMGs generally improved with increasing Cr/Mo content. The sample Cr15 Mo4 exhibited the highest corrosion resistance with a self-corrosion and passivation current density ∼10 −8 A·cm −2 and ∼10 −6 A·cm −2, respectively. X-ray photoelectron spectroscopy of the samples revealed that compared to Cr15 Mo4, there was a higher proportion of defective high-valence metal cation (Fe 3+, Cr 6+, and Mo 6+ ) oxides and a lower proportion of stable low-valence metal cation (Fe 2+, Cr 3+, and Mo 4+ ) oxides in the passive films of Cr20 Mo4 and Cr15 Mo8 . This explains the reason why adding more than 15 at.% Cr and 4 at.% Mo degrades the corrosion resistance of the Fe-based BMGs. The dry sliding wear test demonstrated that the Fe-based BMGs exhibited significantly better wear performance than 316L SS and 304L SS. The wear rate and coefficient of friction of the Fe-based BMGs decreased with increasing Cr/Mo content. The sample Cr15 Mo8 exhibited the lowest wear rate and coefficient of friction of 0.98 × 10 −5 mm 3 ·N −1 ·m −1 and 0.38, respectively. The Fe-based BMGs synthesized in this work, especially Fe61 Cr15 Mo4 P10 C7 B3, exhibited a high GFA and excellent corrosion and wear resistance. Therefore, they have immense potential for various engineering applications. Highlights: A series of novel Fe–Cr–Mo–P–C–B bulk metallic glasses (BMGs) with critical diameters in the range of 1.0–2.5 mm were fabricated by copper mold casting. The corrosion resistance of the Fe-based BMGs is much better than that of 316L SS and 304L SS, and generally improved with increasing Cr/Mo content. The Fe-based BMG of 15 at.% Cr and 4 at.% Mo exhibits the highest corrosion resistance with a self-corrosion and passivation current density ∼10 −8 A·cm −2 and ∼10 −6 A·cm −2 . Adding more Cr/Mo relative to 15 at.% Cr and 4 at.% Mo degrades the corrosion resistance of the Fe-based BMGs. The coefficient of friction and wear rate of the Fe–based BMGs are much lower than of 316L SS and 304L SS, and decrease with the increase of Cr/Mo content.